The Arthur of medieval Latin literature : the development and dissemination of the Arthurian legend in medieval Latin - Echard, Siân (Arthurian literature in the Middle Ages, 2011)
King Arthur's stories survive in many genres, but while scholars and enthusiasts alike know something of his roots in Geoffrey of Monmouth's Latin History of the Kings of Britain, most are unaware that there was a Latin Arthurian tradition which extended beyond Geoffrey. This collection of essays highlights different aspects of that tradition.